Simultaneous Determination of RDX and HMX in Rat Plasma by LC-MS/MS and its Applications - Zhang, Xi; An, Zhuoling; Lv, Yali; Li, Guangrun; Liu, Lihong; Li, Pengfei (Frontiers in Chemistry, 2022)
Background:1,3,5-trinitroperhydro-1,3,5-triazine (RDX) and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) can cause serious toxicity problems in humans and animals, but direct analyses of RDX and HMX in biological samples are very limited. A rapid and efficient liquid chromatography-electrospray quadrupole linear ion trap mass spectrometry (LC-MS/MS) method suitable for the simultaneous determination of RDX and HMX in rat plasma after intravenous administration of two nitramine compound mixed solutions has been developed. Methods: Plasma samples were pretreated with one-step protein precipitation, the plasma consumption is as low as 100 μL. RDX, HMX, and internal standard mycophenolic acid were eluted for 8.0 min on a reversed-phase C18 analytical column with a water/acetonitrile mixture as the mobile phase. An electrospray ionization (ESI) source was applied and operated in negative ion mode. The optimized mass transition ion pairs (m/z) monitored for RDX, HMX, and internal standard mycophenolic acid were m/z 284.1→61.7, m/z 331.0→108.8, and m/z 319.2→191.1, respectively. Results: The detection ranges of both RDX and HMX in plasma were 5.00-200.00 ng•mL-1 with an LOD of 1.00 ng•mL-1. The extraction recoveries of RDX and HMX were 60.04±4.18% and 79.57±3.35%, respectively. The precision and accuracy met the requirements, and the method was stable under all tested conditions. Conclusion: The present method is miniaturized, effective, portable, rapid and can be easily used for simultaneous quantification of RDX and HMX in rat plasma.